2014
DOI: 10.1111/hel.12128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tailored Helicobacter pylori Eradication Treatment Based on Clarithromycin Susceptibility and Maintenance of Acid Secretion

Abstract: A tailored H. pylori eradication regimen based on CAM susceptibility and maintaining acid secretion (rabeprazole 10 mg q.i.d.) is useful because it can achieve an eradication rate exceeding 95%, irrespective of eradication history, thus overcoming differences among CYP2C19 genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…MNZ based conventional triple therapy has sufficiently high eradication success rate in Japan[3-7]. It has been reported that sufficient acid inhibition during eradication was more important in CAM based regimen than MNZ[15]. Therefore, we could not show the difference in secondary eradication therapy between the PPI group and the vonoprazan group.…”
Section: Discussionmentioning
confidence: 84%
“…MNZ based conventional triple therapy has sufficiently high eradication success rate in Japan[3-7]. It has been reported that sufficient acid inhibition during eradication was more important in CAM based regimen than MNZ[15]. Therefore, we could not show the difference in secondary eradication therapy between the PPI group and the vonoprazan group.…”
Section: Discussionmentioning
confidence: 84%
“…In a tailored regimen, H. pylori patients with clarithromycinsensitivity were treated with clarithromycin, amoxicillin, rabeprazole, while clarithromycin-resistant patients were treated with metronidazole, amoxicillin, rabeprazole for 1 wk. As a result, the overall eradication rate was 96.7% (95%CI: 92.5%-98.9%) by ITT analysis and 97.4% (95%CI: 93.4%-99.3%) by PP analysis [148] . The method achieved high eradication rates of 94.3% in CYP2C19 rapid metabolizers [148] .…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 96%
“…As a result, the overall eradication rate was 96.7% (95%CI: 92.5%-98.9%) by ITT analysis and 97.4% (95%CI: 93.4%-99.3%) by PP analysis [148] . The method achieved high eradication rates of 94.3% in CYP2C19 rapid metabolizers [148] . Although CYP2C19 genotyping remains difficult clinically, tailored therapy may be useful in overcoming decreased eradication rates.…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 96%
See 1 more Smart Citation
“…In Japan, as the first-line H. pylori eradication therapy, a triple regimen consisting amoxicillin, clarithromycin, and a proton pump inhibitor (PPI) or vonoprazan is used, whereas the incidence rate of clarithromycin-resistance H. pylori strain is higher than 35% [17, 18]. However, because the maximum blood concentration and half-life time (t 1/2 ) of amoxicillin significantly differ between hemodialysis patients and non-dialysis patients [19], the efficacy and safety of conventional eradication regimens for hemodialysis patients have not yet been established.…”
Section: Introductionmentioning
confidence: 99%